PATTERNS OF FUNDUS AUTOFLUORESCENCE DEFECTS IN NEOVASCULAR AGE-RELATED MACULAR DEGENERATION SUBTYPES. Issue 11 (November 2016) - Ozkok, Ahmet; Sigford, Douglas K.; Tezel, Tongalp H.
Abstract : Purpose: To test define characteristic fundus autofluorescence patterns of different exudative age-related macular degeneration subtypes. Methods: Cross-sectional study. Fifty-two patients with choroidal neovascularization because of three different neovascular age-related macular degeneration subtypes were included in the study. Macular and peripheral fundus autofluorescence patterns of study subjects were compared in a masked fashion. Results: Fundus autofluorescence patterns of all three neovascular age-related macular degeneration subtypes revealed similar patterns. However, peripapillary hypo-autofluorescence was more common among patients with polypoidal choroidal vasculopathy (88.2%) compared with patients with retinal angiomatous proliferation (12.5%) and patients without retinal angiomatous proliferation and polypoidal choroidal vasculopathy (21.1%) ( P < 0.0001). Conclusion: Presence of peripapillary fundus autofluorescence defects in neovascular age-related macular degeneration maybe suggestive of polypoidal choroidal vasculopathy as a variant of neovascular age-related macular degeneration. Abstract : This study presents the evaluation fundus autofluorescence defect patterns and localization of different neovascular age-related macular degeneration (nAMD) subtypes. Fundus autofluorescence patterns of all three nAMD subtypes revealed similar patterns; however, peripapillary autofluorescence defects were significantly more common in cases with polypoidal choroidal vasculopathy.